Case Report: Rare Case of Staphylococcus pasteuri Endocarditis. (25th March 2023) - Merrild, Esben; Winther, Mette; Dahl, Jonathan Nørtoft; Ebsen, Tine Sneibjerg; Leth, Steffen; Winther, Simon
Abstract : A 45-year-old woman was admitted with severe pain in the right leg and dyspnea. Her medical history included previous Staphylococcus aureus endocarditis, biological aortic valve replacement, and intravenous drug abuse. She was febrile but did not have any focal signs of infection. Blood tests showed raised infectious markers and troponin levels. Electrocardiogram showed sinus rhythm without signs of ischemia. Ultrasound revealed thrombosis of the right popliteal artery. The leg was not critically ischemic, and therefore, treatment with dalteparin was chosen. Transesophageal echocardiography showed an excrescence on the biological aortic valve. Empiric treatment for endocarditis was started with intravenous vancomycin, gentamicin, and oral rifampicin. Blood cultures subsequently grew Staphylococcus pasteuri . On day 2, treatment was changed to intravenous cloxacillin. Due to the comorbidity, the patient was not a candidate for the surgical treatment. On day 10, the patient developed moderate expressive aphasia and weakness in the right upper limb. Magnetic resonance imaging showed micro-embolic lesions scattered across both hemispheres of the brain. Treatment was changed from cloxacillin to cefuroxime. On day 42, infectious markers were normal, and echocardiography showed regression of the excrescence. Antibiotic treatment was stopped. Follow-up on day 52 did not show any signs of active infection. However, on day 143, the patient was readmitted with cardiogenic shock due to aortic root fistulation to the left atrium. She quickly deteriorated and died.